Framing the Central Bank Digital Currency (CBDC) revolution - Ozturkcan, Selcen; Senel, Kerem; Ozdinc, Mesut (Technology analysis & strategic management, 2025)
As global cooperation to develop and launch CBDCs further unfolds, the revolutionary innovation presents an emerging research field. This paper aims to provide a framework of CBDC by stressing its differences from other available digital currencies and cash in terms of advantages and disadvantages. The CBDC outlook, in its current and future, is presented. Additionally, an exploration of the prevalent themes in a cross-sectional analysis of tweets posted between 17 and 25 March 2021 with the #CBDC hashtags are presented to complement the discussion on the emerging landscape for informing the policy - and decision-makers on the opportunities and challenges involved.